(3SQGL GdeQjOjf aj SHjd GdOjfs - (3eMeO Hf YHO Gddg Hf eMeO GdeYGaQj GdETHjdj GdeGdcj, GdbGVj CHh HcQ GHf GdYQHqj , J (B543 (3g` s ((3OGQ GdSfI (B_ (3eOjfI OeTb s)
(3ChdgG (B:s
(3jHOC HGdebGe GdChd ai Gd MjGI GdOfjG hai MGd GdEfSGf hMGd GdfHi Udi Gddg Ydjg hSde hGUMGHg s
(3BNQgG (B:s
(3jfJgi HGdebGeI GdSGOSI YTQ heFg GdEHOGd Ke PcQ GdCNHGQ GdhGQOI ai GdEHOGd hgj NGJeI GdcJGH s
(3GdbSe GdQGHY ai Ydhe GdbQBfs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B230 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B242s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B984s
Keywords: (3GdJUha hGdBOGH GdTQYjIs